(untitled) (Altre Modernità, 2019)
This article proposes an approximation to the least known literary work of the Cuban female poet Mercedes Matamoros (1851-1906). The article considers her as a modernist for several reasons, which will be explored. In particular, several critical positions about Matamoros are examined and two poems of the collection Por el camino triste, which were published in the newspaper Diario de la Marina in 1904, are analysed. These almost unknown poems were published by Catharina Vallejo in 2004 in the edition Poesías of the Cuban woman poet.